PENGARUH KEPEMIMPINAN TERHADAP PRODUKTIVITAS KERJA PADA KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI (KPPBC) TIPE MADYA PABEAN B PEKANBARU - Magdalena Purba; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The purpose of this study was to determine the effect of leadership on work productivity at the Customs and Excise Supervision and Service Office (KPPBC) of Madya Pabean B Pekanbaru. This research was conducted at the Customs and Excise Supervision and Service Office (KPPBC) of Madya Pabean B Pekanbaru, located on Jenderal Sudirman Street No. 2-4 Senapelan Pekanbaru. In this research method the method used is a statistical test with the SPSS program, where the sample used is employees and the community working area of the Customs and Excise Supervision and Service Office (KPPBC) of Madya Pabean B Pekanbaru. To determine the a questionnaire. The population and sample in this study were equal to 108 respondents consisting of the Customs and Excise Supervision and Service Office (KPPBC) of Madya Pabean B Pekanbaru. From the results of data analysis which includes validity test, reliability test, correlation test and coefficient of determination show that leadership has an influence on work productivity at the Customs and Excise Supervision and Service Office (KPPBC) of Madya Pabean B Pekanbaru with a value of 0.858 means that the influence of leadership variables on work productivity variables is 85.8%. The results of testing the hypothesis found that t-count is greater than t-table which means Ha is accepted.Keywords: Leadership and Work Productivity